Adsorptive removal of phosphorus(V) and chromium(VI) oxyanions using thermally treated titanium-rich bauxite. Issue 32 (8th July 2016) - Behera, R.K.; Das, R.
Abstract: The removal of P(V) and Cr(VI) oxyanions from their aqueous solution by batch adsorption technique using raw and heat-treated titanium-rich bauxite (TRB) of Jobhipat bauxite mines, Jharkhand, India, was investigated under varying experimental parameters. TRB, calcined at 450°C (TRB-450), showed maximum uptake of both the oxyanions from their aqueous solutions. Adsorption process was found to be highly pH dependent. The optimum pH range for maximum P(V) adsorption was 4.5–5.0 while highest adsorption of Cr(VI) was observed at lower pH (~3.0) which progressively decreased on further increase of pH. Kinetic studies in the temperature range 30–50°C revealed the adsorption of both the oxyanions were best fitted with pseudo-second-order kinetic model and Langmuir adsorption isotherms. The derived Gibbs's free energy (Δ G °) values indicated a spontaneous adsorption process for both the oxyanions, and the adsorption of P(V) ion was favoured at higher temperature while ~40°C was found to be the optimum temperature for adsorption of Cr(VI) oxyanion. The adsorption of both oxyanions was significantly affected in the presence of bivalent anion like ions and . The present set of data provided further input to assess the potential of naturally occurring TRB towards the removal of different toxic ions from contaminated water.